Framing Floods: A Qualitative Analysis of Jakarta Flood Coverage in Indonesian Online Media - Mas Davino Sayaza; Tazkialaras (Jurnal Rekayasa Lingkungan dan Biosistem, 2025)
This study examines how Indonesian online media framed the Jakarta floods in 2024 using framing theory, agenda-setting theory, and attribution theory. Through qualitative content analysis of ten news articles from two major online portals, the research identifies dominant frames, causal attributions, and implications for public discourse. Findings reveal that 80% of articles framed floods as natural disasters caused primarily by weather conditions (90%), while only 30% mentioned infrastructure inadequacy. Government sources dominated coverage with consistently positive framing, and 100% of articles emphasized emergency response while only 20% discussed long-term solutions. The study contributes to environmental communication scholarship by documenting how Indonesian media construct flood narratives and extending disaster framing research to the Southeast Asian context.